2021
DOI: 10.1038/s41598-021-86740-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-controlled serine protease inhibitor (serpin) production in Bifidobacterium longum subsp. longum

Abstract: The Serine Protease Inhibitor (serpin) protein has been suggested to play a key role in the interaction of bifidobacteria with the host. By inhibiting intestinal serine proteases, it might allow bifidobacteria to reside in specific gut niches. In inflammatory diseases where serine proteases contribute to the innate defense mechanism of the host, serpin may dampen the damaging effects of inflammation. In view of the beneficial roles of this protein, it is important to understand how its production is regulated.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The primary endpoints considered were assessments of symptom severity with IBS-SSS, an improvement of IBS symptoms using the global improvement scale (IBS-GIS), and adequate relief of symptoms after four and eight weeks of therapy. An earlier study found that increasing doses of scFOS were associated with an increase in concentrations of fecal bifidobacteria [ 97 ], which have beneficial effects on colonic pH regulation, favorable immune modulation, pathogen exclusion, increasing SCFA production, and anti-protease production [ 98 ]. In general, the consumption of synbiotics by IBS patients has been associated with improvements in overall IBS/health-related quality of life (outcomes: frequency and severity of pain, bloating severity, bowel movement frequency, and satisfaction).…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…The primary endpoints considered were assessments of symptom severity with IBS-SSS, an improvement of IBS symptoms using the global improvement scale (IBS-GIS), and adequate relief of symptoms after four and eight weeks of therapy. An earlier study found that increasing doses of scFOS were associated with an increase in concentrations of fecal bifidobacteria [ 97 ], which have beneficial effects on colonic pH regulation, favorable immune modulation, pathogen exclusion, increasing SCFA production, and anti-protease production [ 98 ]. In general, the consumption of synbiotics by IBS patients has been associated with improvements in overall IBS/health-related quality of life (outcomes: frequency and severity of pain, bloating severity, bowel movement frequency, and satisfaction).…”
Section: Intestinal Epithelial Barrier Disordersmentioning
confidence: 99%
“…Bifidobacteria are natural inhabitants of the human gut and are known to display immunomodulatory properties. Members of this genus revealed a large repertoire of genes enabling their adaptation and resistance to the hostile GIT environment [ 134 , 135 , 136 ]. Among them, serpins are described to be involved in this interaction.…”
Section: Serpins Natural Inhibitors To Control the Activity Of Serine Proteasesmentioning
confidence: 99%
“…Nevertheless, sequencing of the genomes of more bifidobacterial species, together with recent advances made by metagenomic analysis, allowed the identification of several additional Bifidobacterial species-encoding serpins [ 121 , 137 ]. Intriguingly, induced transcription of Bifidobacterial serpins in response to different environmental conditions in the GIT has been highlighted [ 134 , 135 ]. This includes the presence of several prokaryotic and eukaryotic proteases [ 135 , 138 ].…”
Section: Serpins Natural Inhibitors To Control the Activity Of Serine Proteasesmentioning
confidence: 99%
“…This notion is further confirmed by our recent study that demonstrated that in B. longum subsp. longum, serpin production is regulated by the carbohydrate-substrates used for growth, revealing galactose and fructose (or galacto-or fructo-di/oligo-saccharides) as inducing substrates, while the presence of glucose repressed serpin production almost completely (Duboux et al, 2021). These studies illustrate the diverse environmental factors and regulatory mechanisms involved in controlling serpin production in Bifidobacterium (sub-) species, indicating that growth conditions (e.g., substrate) could be tailored to ensure, or even enhance the production and function of this NF and/or EM in the final probiotic preparation.…”
Section: Environmental Factors Regulating Serine Protease Inhibitor Productionmentioning
confidence: 99%